Learning Democracy through Self-governance: The Case of Housing Co-operative - Karsten Mündel; Fiona Duguid; Daniel Schugurensky (Adult Education Research Conference, 2004)
Housing co-operatives are a unique site to learn democracy through participation in self-governance by volunteering on boards and committees. Members reported both nonformal and informal learning; the latter was particularly significant for the development of skills, knowledge, attitudes and values required for effective democratic participation.